LNG, climate and energy security: Towards a comprehensive approach for Europe - Felix Heilmann; Janek Steitz; Simon Müller; Philippa Sigl-Glöckner (Dezernat Zukunft e.V., 2023)
Europe, and Germany in particular, have quickly ramped up liquefied natural gas (LNG) imports to partially offset the loss of Russian pipeline gas deliveries. While many observers rightly applaud this historical achievement, there are also concerns that LNG decisions taken in the face of the crisis can lead to new, risky path dependencies incompatible with climate safeguards. This paper seeks to build bridges and inform more nuanced deliberations. It does so by exploring in detail relevant aspects along the LNG supply chain, guided by the principal assumption that both climate goals and energy security must be achieved. It has been informed by extensive stakeholder engagement, including a workshop bringing together different experts. We find that the development of new LNG export terminals that have not yet reached a final investment decision poses the biggest risk of violating climate targets. In contrast, European import terminals can act as back-up capacities for crisis times. For this, their use needs to be restricted during non-crisis periods. In terms of LNG market balancing, large new export projects currently under development are already set to enter operation before 2027, significantly easing currently tight markets. Additional export capacity beyond this cannot contribute to easing the current supply crunch at scale given long development times and risks ending up as stranded assets. Europe should therefore refrain from supporting new upstream projects, including through longterm contracts that enable such projects, and instead focus contracting efforts on the growing amount of uncontracted volumes from expiring legacy contracts, portfolio players, and from export projects that have already reached final investment decisions. Short- and medium-term contracts could decrease uncertainties resulting from excessive spot market exposure while limiting climate risks. There may be a role for governments to enable such contracts. Lastly, there are two no-regret strategies. In the short term, tackling methane emissions can deliver significant climate and energy security benefits. In the long term, only phasing out natural gas by transitioning to efficient renewable energy systems ultimately reconciles energy and climate security.
Keywords: 330